Narrative Review on the Therapeutic Approach to Violence against Women during the COVID-19 Pandemic in Latin America - Cjuno, Julio (2023)
Violence against women during the pandemic has become a problem that has affected the world and to date has caused the death of many women. Although mental health has shown a growing interest in research, it is still very susceptible to being affected. This research described the scientific literature on the challenges in the psychotherapeutic approach in victims of violence against women during the COVID-19 pandemic in Latin America. A narrative review was carried out with a search of documents in the Scopus, Web of Science and PubMed databases, using descriptors for women, violence against women, COVID-19 and Latin America. As a result, 12 studies were included, which reported that the use of helplines, digital platforms of care and teletherapy were advantageous in several Latin American countries during the pandemic; difficulties were found in the accessibility of care for cases, collapse of telephone lines, technical problems of the system and the need for training for health professionals and service providers. It can be concluded that the coping strategies most used during the pandemic were the help services, through telephone and virtual care; there was difficulty in following up and monitoring the case in the medium and long terms, so further studies could focus on it. The main limitation of this work is methodological, since a number of studies could have been excluded from the searches for not including some of the terms in the search equation.